Is the following statement true or false?
c 2 a b + a 2 b c + b 2 c a = 3 ⟺ c a + b + a b + c + b c + a ∈ { − 3 ; 6 }
a + b + c = 0
This is part of the set: It's easy, believe me!
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Notice that c 2 a b + a 2 b c + b 2 c a = 3 implies that, for x = a b , y = b c , z = c a :
x 3 + y 3 + z 3 − 3 x y z = 0 ↔ ( x + y + z ) ( ( x − y ) 2 + ( y − z ) 2 + ( z − x ) 2 ) = 0 .
This implies that either a b + b c + c a = 0 ( 1 ) or a = b = c ( 2 ) .
We easily find, by applying (1), c a + b = − c 2 a b a c + b = − a 2 b c b a + c = − b 2 a c
and we finally find that c a + b + a c + b + b a + c = − ( c 2 a b + a 2 b c + b 2 a c ) = − 3
by the original equation.
c a + b + a c + b + b a + c = 6
Hence the result follows. □